The Sunscreen activities of ethanol, ethyl acetate, n-hexane, and water fractions from papaya (Carica papaya l.) leaf extract - Wardatun, Sri; Mahyuni, Siti; Setiawan, Putra (Universitas Padjadjaran (Unpad), 2023)
The application of sunscreen products containing natural compounds is one ofalternative popular ways to protect the skin from the harmful effects of sunexposure. The aim of this study was to evaluate the sunscreen activity of papayaleaf extract. The ethanol extract of papaya leaf was fractionated to obtain ethanol,n-hexane, ethyl acetate, and water extracts. The value of SPF 15, percenttransmission of erythema (1% Te ), and the percent transmission of pigmentation40 (% Tp) of each extract were calculated in vitro by using spectrophotometricmethod. among the extract examined, the ethyl acetate extract was found to be themost effective to reach Sun Protection Factor (SPF) 15 (ultra-protection category)and 1% Te (sunblock category) at a minimum concentration of 90.08 ppm and63.49 ppm. Meanwhile n-hexane extract was the most effective to reach 40% tp(sunblock category) at a minimum concentration of 30.68 ppm. The minimumconcentration of papaya leaf extracts required to reach SPF 15, 1% Te and 40% Tpwere far below the concentration of sunscreen compounds allowed in commercialcosmetic products. It can be concluded that papaya leaf extract have significantsunscreen property for use as cosmetic ingredient.Keywords: Carica papaya, SPF, Transmission of erythema, Transmission ofpigmentation